DOP66 Surveillance colonoscopies in ulcerative colitis: does it make a difference?. (25th January 2019) - Hu, A; Nguyen, G; Rangrej, J; Marshall, J; Narula, N
Abstract: Background: Patients with ulcerative colitis (UC) and Crohn's disease (CD) have a higher risk of colorectal cancer compared with the general population. Surveillance colonoscopy for detection of dysplasia is advised; however, the ideal intervals for surveillance have not been established. This study aims to identify the association between colonoscopy surveillance intervals for UC patients in Ontario and the incidence and CRC stage. Methods: This study was approved by the Ontario Institute for Clinical Evaluative Sciences (ICES), which permitted access to data from the Ontario Cancer Registry (OCR) and Ontario Health Insurance Plan (OHIP) claims. This allowed us to retrospectively identify UC patients diagnosed from 1994 onwards with an OHIP billing code 556 and their incidence of CRC with an OHIP billing code 153. The primary endpoint was CRC stage at the time of CRC diagnosis compared between patients who did not have screening colonoscopies, average screening interval ≤3 years and an average screening interval >3 years. We defined low-risk CRC stage as patients according to the Cancer Care Society (CCS) to have a 5-year survival >80% compared with high-risk CRC as patients with 5-year survival <80%. According to CCS, CRC stages I, IIa, III and IIIa were classified as low-risk and CRC stages IIb, IIc, IIIb, IIIc, IIINOS, IV were high risk. Analysis was conducted using SAS 9.4 statistical software. Chi-square testing was used to compare frequencies. Results: Within the ICES database, a total of 631 UC patients developed CRC and 264 of them had staging information available. Among these patients, those who had average follow-up colonoscopies at a frequency ≤ 3 years presented with an earlier stage of CRC (58.6% of the time) compared with those with follow-up colonoscopies at a frequency > 3 years (44% of the time) and those with no follow-up colonoscopies (18.5% of the time) (Mantel–Haenszel chi-square p -value < 0.001). In addition, mortality benefit was observed at 15-years after time of eligibility for surveillance colonoscopies, with survival seen in 75.1% of UC patients who had CRC and average colonoscopies ≤ 3 years, compared with 70.1% in the average colonoscopies > 3 years cohort and 57.8% in the no colonoscopy surveillance cohort ( p = 0.004). Conclusions: UC patients who underwent colonoscopies at average intervals of ≤ 3 years had CRC detected at earlier stages compared with those who underwent colonoscopies at >3 year intervals or those who did not have follow-up colonoscopies. Mortality benefit was also observed in those patients with UC and CRC who had colonoscopies at average intervals ≤ 3 years. This supports a surveillance interval for UC of ≤ 3 years.